THE EFFECT OF WORK-LIFE BALANCE ON INTENTION TO STAY MEDIATED BY PSYCHOLOGICAL EMPOWERMENT - Intan Nur Sofia; Walyoto Walyoto (Journal of Management and Islamic Finance, 2021)
This study was intended to analyze the effect of supervisor support and job autonomy on the intention to stay. This study also examines the effect of psychological empowerment on the intention to stay. The sampling method used was non- probability sampling with the samples of female nurses in all hospitals in the Sragen Regency. The analysis used the Structural Equation Model (SEM) Software using AMOS 22 to test and estimate the causal relationship of a combination of statistical data and qualitative causal assumption data. The results of the SEM analysis of 187 respondents showed that there was a significant effect of psychological empowerment on supervisor support and intention to stay. However, psychological empowerment cannot bridge the effect of job autonomy and the intention to stay. Furthermore, this study also shows that variable of the supervisor support is the most significant variable in affecting psychological empowerment compared to job autonomy. Thus, the best strategy in increasing the desire of employees to stay in the company is to increase supervisor support and psychological empowerment.